Serum ?-Klotho Level in the Patients Subjected to Hemodialysis in Association with Lipid Profile (Medico Legal Update, 2020)
Background: Klotho, is a protein associated with life extension plays a important role in kidney disease progression, anti-aging, anti-oxidation, modulation of ion transport, and development of disturbed mineral metabolism. The aim of the study was to measure Soluble ?-Klotho(SAKL) levels in chronic kidney disease(CKD) patients before and after dialysis in relation with Lipid profile. Methods: This short-prospective hospital-based study was done in the Department of Chemistry and Biochemistry, College of medicine, Tikrit University, Tikrit, Iraq. The study was carried out for 30 patients subjected to Hemodialysis recruited from Tikrit Teaching Hospital, hemodialysis unit between 1st December,2018 and 1st April,2019. The study also included 30 adult persons looks healthy with no prior medical or family history of CKD as a control participated in this study.The levels of SAKL and lipid profile were measured in the serum of 30 patients, before and after Hemodialysis and compared with controls. Results: The study revealed increased in the SAKL level in CKD patients before dialysis compared to healthy control group, and decreased in group of CKD after dialysis compared to control group. Furthermore, there was a significant positive correlation of SAKL level with serum Triglyceride and Very low density lipoprotein cholesterol(VLDL-C) in CKD patients before dialysis. Conclusions: There was a highly significant relation of SAKL with lipid abnormality in CKD patients under hemodialysis.